PENGARUH BANTUAN INTER-AMERICAN DEVELOPMENT BANK (IADB) DALAM PROGRAMA NACIONAL DE ELECTRIFICACIÃ“N SOSTENIBLE Y ENERGÃA RENOVABLE (PNESER) TERHADAP SEKTOR ENERGI LISTRIK DI NIKARAGUA TAHUN 2010 - Sari, Nopita; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Nicaragua has two major problem on its electricity sector. Nicaragua is the country with lowest electricity coverage rate in the region and high dependence on using fossil as source of electrical energy. In the other side Nicaragua did not have enough development fund because of the accumulation of political conflict in the country. This research will describe about the influence of the Inter-American Development Bank’s (IADB) assistance that applied in a program called Programa Nacional de Electrificación Sostenible y Energia Renovable (PNESER) for the development of the electricity sector in Nicaragua.As for the methode used in the study is qualitative research. The data obtained from literature in the form of books, documents, journals, newspapers, internet and other media that related to the issues. To analyze the case, this research will be based on the perspective of Structuralism and Dependency theory.This research show that IADB’s assistance can bring several positive effect for Nicaragua’s electricity sector. Within a few years, the sector modernized and improve the electricity coverage in the country. The Assistance that also earmarked for the development of renewable energy sources has also significantly increase the production of renewable energy sources in the country. But all of this positive effect cause another problem, it makes Nicaragua become a country that have high dependence on foreign party.Keyword: Electricity Sector, PNESER, Production Growth, Electricity Coverage, Renewable Energy, Dependency